Introduction to Iranian Blood Transfusion Organization and Blood Safety in Iran - H Abolghasemi; M Maghsudlu; S Amini Kafi-Abad; A Cheraghali (Tehran University of Medical Sciences, 2009)
"nCurrently, in Iran blood transfusion is an integral part of the national health system and blood donation is voluntary and nonremunerated and blood and its components may not be a source of profit. In 1974 and following establishment of Iranian Blood Transfusion Organization (IBTO) all blood transfusion activities from donor recruitment to production of blood components and delivery of blood and blood products were centralized. The activities of IBTO are followed the laws and regulations of Ministry of Health and criteria of Iran National Regulatory Authority. In order to meet the country's demand in 2007 IBTO collected about 1.7 millions units of blood from the population of 70 millions. In 1979 coincided with the Islamic revolution the number of  blood units collected throughout the country were 124,000 units or 3.4 unit per 1000 population whereas after about 30 years this increased to about 25 unit per 1000 population. With improving the pool of voluntary donors, IBTO has been successful in excluding "family replacement" donation since 2007 and reached to 100% voluntary and nonremunerated blood donation. Currently more than 92% of blood donors in Iran are male and contribution of female in blood donation is less than 8%. Although all donated blood in Iran screened for HBsAg since 1974, screening of blood units for HIV and HCV started since 1989 and 1996, respectively. The frequency of HBV infection in blood donors showed a significant decline from 1.79% in 1998 to 0.4% in 2007. The overall frequency of HCV and HIV infection are 0.13% and 0.004% respectively.